DOI: 10.18130/v38w2h
|View full text |Cite
|
Sign up to set email alerts
|

The role of sex ratio as a context for selection in Silene vulgaris

Abstract: When the sex ratio varies among populations, it is likely that the fitness consequences of sexual phenotypes will also differ among those populations. Sex ratio can also vary at a fine scale within populations, and so there may be multiple, potentially overlapping scales over which sex ratio can affect the evolutionary process. I explored the fitness consequences of sex ratio variation in Silene vulgaris, a perennial herb that maintains a sexual polymorphism between plants that produce both pollen and seed, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 50 publications
(75 reference statements)
0
2
0
Order By: Relevance
“…It must be noted that the interactions we observed are not representative of all gynodioecious systems, of all populations of S. vulgaris , or even across all years at the same site. Similar experiments on S. vulgaris at the same site but in different years failed to find significant differences between nocturnal and diurnal pollinators (Sanderson, ), indicating the potential for temporal variation in pollinator services to influence the maintenance of gynodioecy. Whereas we recorded no seed predation at our site, nocturnal pollinators in Silene's European range, particularly from the genus Hadena , are known to act as seed predators that may shift the pollination interaction from mutualistic towards parasitic (Pettersson, ; Giménez‐Benavides et al ., ).…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…It must be noted that the interactions we observed are not representative of all gynodioecious systems, of all populations of S. vulgaris , or even across all years at the same site. Similar experiments on S. vulgaris at the same site but in different years failed to find significant differences between nocturnal and diurnal pollinators (Sanderson, ), indicating the potential for temporal variation in pollinator services to influence the maintenance of gynodioecy. Whereas we recorded no seed predation at our site, nocturnal pollinators in Silene's European range, particularly from the genus Hadena , are known to act as seed predators that may shift the pollination interaction from mutualistic towards parasitic (Pettersson, ; Giménez‐Benavides et al ., ).…”
Section: Discussionmentioning
confidence: 78%
“…Alonso (2004) and Barthelmess et al (2006) demonstrated the practicality of experimentally manipulating pollinator guilds to study the effects of their component groups in gynodioecy-rich lineages. Direct evidence of pollinators' influence on female advantage by measuring both sexes' seed production in multiple pollination contexts, however, remains limited (Ashman, 2006;Dufa€ y & Billard, 2012;Sanderson, 2016). Alonso (2004) reported variation in female and hermaphrodite fruit set associated with pollinator exclusion in Daphne laurelola, but found no significant sex-by-pollination treatment effects.…”
Section: Introductionmentioning
confidence: 99%